Coping With Changes to Sex and Intimacy After a Diagnosis of Metastatic Breast Cancer: Results From a Qualitative Investigation With Patients and Partners - Reese, Jennifer Barsky; Zimmaro, Lauren A.; McIlhenny, Sarah; Sorice, Kristen; Porter, Laura S.; Zaleta, Alexandra K.; Daly, Mary B.; Cribb, Beth; Gorman, Jessica R. (Frontiers in Psychology, 2022)
Objective: Prior research examining sexual and intimacy concerns among metastatic breast cancer (MBC) patients and their intimate partners is limited. In this qualitative study, we explored MBC patients’ and partners’ experiences of sexual and intimacy-related changes and concerns, coping efforts, and information needs and intervention preferences, with a focus on identifying how the context of MBC shapes these experiences. Methods: We conducted 3 focus groups with partnered patients with MBC [N=12; M age=50.2; 92% White; 8% Black] and 6 interviews with intimate partners [M age=47.3; 83% White; 17% Black]. Participants were recruited through the Fox Chase Cancer Center Tumor Registry and the Cancer Support Community. Qualitative data were analyzed using the Framework Method and Dedoose software. Results: Qualitative analyses revealed several key themes reflecting ways in which MBC shapes experiences of sex/intimacy: (1) the heavy disease/treatment burden leads to significant, long-term sexual concerns (e.g., loss of interest, vaginal dryness/discomfort) and consequent heightened emotional distress for both patients (e.g., guilt around not being able to engage in intercourse) and partners (e.g., guilt around pressuring the patient to engage in sexual activity despite pain/discomfort); (2) viewing the relationship as having “an expiration date” (due to expected earlier mortality) influences patients’ and partners’ concerns related to sex/intimacy and complicates coping efforts; and (3) information needs extend beyond managing sexual side effects to include emotional aspects of intimacy and the added strain of the life-limiting nature of the disease on the relationship. The heightened severity of sexual concerns faced by patients with MBC, compounded by the terminal nature of the disease, may place patients and partners at risk for significant adverse emotional and interpersonal consequences. Conclusions: Findings suggest unique ways in which sex and intimate relationships change after a diagnosis of metastatic breast cancer from both patients’ and partners’ perspectives. Consideration of the substantial physical and emotional burden of MBC and the broader context of the relationship and intimacy overall is important when developing a sexuality-focused intervention in this population. Addressing sexual concerns is a critical part of cancer care with important implications for patients’ health and quality of life.